COVID-19: PATHOGENESIS IN THE IMMUNE, METABOLIC, CARDIOVASCULAR SYSTEM: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article analyzes the pathogenesis of the disease, physiological mechanisms and, of course, the post-COVID-19 recovery period. Analyzed quantitative changes in metabolism in the body, the dynamics of clinical signs. The research used more than 50 articles from the leading database, the information obtained from them is clearly explained.